BasS/BasR Two-Component System Affects the Sensitivity of Escherichia coli to Plantaricin BM-1 by Regulating the Tricarboxylic Acid Cycle - Liu, Yifei; Wang, Yawen; Chen, Xinyue; Jin, Junhua; Liu, Hui; Hao, Yanling; Zhang, Hongxing; Xie, Yuanhong (Frontiers in Microbiology, 2022)
Plantaricin BM-1, a class IIa bacteriocin produced by Lactiplantibacillus plantarum BM-1, exhibits significant antibacterial activity against many gram-positive and gram-negative bacteria. However, the mechanism underlying the action of class IIa bacteriocins against gram-negative bacteria remains to be explored. This study aimed to investigate the role of the BasS/BasR two-component system in Escherichia coli K12 response to plantaricin BM-1. The IC50 values for plantaricin BM-1 in E. coli K12, basS mutant (E. coli JW4073), and basR mutant (E. coli JW4074) strains were found to be 10.85, 8.94, and 7.62 mg/mL, respectively. Growth curve experiments showed that mutations in the BasS/BasR two-component system led to an increase in the sensitivity of E. coli K12 to plantaricin BM-1 and that after gene complementation, the complemented mutant strain regained its original sensitivity. Proteomic analysis showed that 100 and 26 proteins were upregulated and 62 and 58 proteins were downregulated in E. coli JW4073 and E. coli JW4074, respectively. These differential proteins, which exhibited different molecular functions and participated in different molecular pathways, were mainly concentrated in the cytoplasm. More specifically, mutations in basS and basR were found to affect the synthesis and metabolism of many substances in E. coli, including many important amino acids and enzymes involved in cellular activities. In addition, 14 proteins, including 8 proteins involved in the tricarboxylic acid (TCA) cycle, were found to be downregulated in both E. coli JW4073 and E. coli JW4074. Growth curve experiments showed that the deletion of these proteins could increase the sensitivity of E. coli to plantaricin BM-1. Therefore, we speculate that TCA pathway regulation may be an important mechanism by which the BasS/BasR two-component system regulates the sensitivity of E. coli to plantaricin BM-1. This finding will facilitate the determination of the mechanism underlying the action of class IIa bacteriocins against gram-negative bacteria.